The Influence of Tourists’ Online Value Co-creation Behavior on Consumer-Brand Relationship Quality: The Moderating Effect of Altruism - Zhang, Yi; Liu, Yue; Tao, Wenxia (Frontiers in Psychology, 2022)
In recent years, there is the popular phenomenon of "grass planting" marketing. The value co-creation behavior of ordinary consumers KOC (key opinion consumer) in the online community is sometimes out of utilitarian intentions, which is deemed as plain people's "grass planting" advertising in a certain degree. We collected the tourists’ data in Chinese Grand Canal National Cultural Park, analyzed the impact of value co-creation behaviors such as tourists’ experience sharing, topic discussions, and suggestions in online communities on the value of tourism experience and the quality of brand relationships under the “planting grass” marketing environment and verified the moderating mechanism of tourist altruism in it. According to the results, tourists' online value co-creation behavior has a significant positive impact on the consumer-brand relationship quality, and experience value plays a mediating role; Tourists' online value co-creation behavior has a significant positive impact on experience value, in which altruism plays a moderating role. The greater the tendency of altruism, the higher the impact of tourists' value co-creation behaviors on their experience value, and vice versa. This conclusion is not only of great significance in deepening and improving theories of value co-creation, altruism, experience value and consumer-brand relationship quality, but also has important certain management enlightenment on how to combine the design of merchant value co-creation incentive mechanism with altruism in "grass planting" marketing.